Examining perspectives of youth participation in Singapore's public decision-making processes - Ong, Clare Jing Wen (Nanyang Technological University, 2023)
Once considered to be apathetic, Singaporean youths have now found their voices, demonstrating an increased desire to participate in public decision-making processes in the domain of politics and beyond. Global studies have highlighted the uses and benefits of youth participation, as well as its many barriers and enablers. Despite increased relevance and interest, few studies have reviewed the state of youth participation in Singapore. Thus, the paper aims to evaluate the effectiveness of the Singapore Government’s ongoing outreach initiatives in encouraging youths to participate via a mixed method case study design. Overall, the survey responses of 114 participants were examined for insights and strengthened with 29 qualitative interviews. Some challenges to youth participation were identified. Primarily, the lack of response to youth participants’ feedback diminished interest to participate. In contrast, a two-way dialogue between the government and citizens facilitates youths’ interest to participate. Critically, it was observed that youths desired to participate in the areas of education, social and/ or cultural policies and general politics. Finally, recommendations to enhance ongoing youth participation initiatives are offered.